Urgensi Pemberantasan Stunting Perspektif Al-Qur'an Surat An-Nisa' Ayat 9 - Witari, Rahmad Alim; Astuti, Efi Tri (Edu Berkah Khatulistiwa, 2024)
This research aims to determine the urgency of eradicating stunting based on Surah An-Nisa' verse 9. This research uses a qualitative approach, in the form of library research as the main method, using sources from the Al-Qur'an, interpretations and data collection techniques through reviewing related documents. . The research results show that based on the Koran, Surah An-Nisa, verse 9, stunting eradication is very important because it has an impact on children's survival in the future. Therefore, efforts to improve the physical health of Muslims through increased nutrition, physical activity, and healthy lifestyles, or other methods, are an integral part of efforts to achieve the main goals of the Shari'a. The results of this research also show that success in eradicating stunting will increase access to quality nutrition, good health services, adequate nutrition education, and high public awareness of stunting prevention itself. From this impact, stunting in Indonesia will decrease and children who do not experience stunting will have better physical and cognitive development, increasing their willingness to learn and productivity in the future.